Prudentópolis geoheritage (Paraná, Brazil) and its potential for the development of geotourism (Terr@ Plural, 2020)
Prudentópolis, located in the southeastern region of the state of Paraná, has a rich geodiversity, addressed in this article in19 geosites with relevant potential for the development of local geotourism. The survey and diagnostic about the geoheritage of Prudentópolis have placed as main factors that could favor the practice of geotourism: i) production of a map of geosites of scientific, didactic and cultural relevance; ii) visitation already exists in most places of interest, with infrastructure; iii) strength interaction between local communities and natural heritage, and; iv) easy access to geosites.
Keywords: Geodiversity; Geoconservation; Geological heritage